Noble Gas Binding Ability of an Au(I) Cation Stabilized by a Frustrated Lewis Pair: A DFT Study - Ghara, Manas; Chattaraj, Pratim Kumar (Frontiers in Chemistry, 2020)
The noble gas (Ng) binding ability of a monocationic [(FLP)Au]+ species has been investigated by a computational study. Here, the monocationic [(FLP)Au]+ species is formed by coordination of Au(I) cation with the phosphorous (Lewis base) and the boron (Lewis acid) centers of a frustrated Lewis pair (FLP). The bonds involving Au and P, and Au and B bonds in [(FLP)Au]+ are partially covalent in nature as revealed by Wiberg bond index (WBI) values, electron density analysis and energy decomposition analysis (EDA). The zero point energy corrected bond dissociation energy (D0), enthalpy and free energy changes are computed for the dissociation of Au-Ng bonds to assess the Ng binding ability of [(FLP)Au]+ species. The D0 ranges from 6.0 to 13.3 kcal/mol which increases from Ar to Rn. Moreover, the dissociation of Au-Ng bonds is endothermic as well as endergonic for Ng = Kr-Rn, whereas the same for Ng = Ar is endothermic but exergonic at room temperature. The partial covalent character of the bonds between Au and Ng bonds is demonstrated by their WBI values and electron density analysis. The Ng atoms get slight positive charges of 0.11-0.23 |e|, which indicates some amount of charge transfer takes place from it. EDA demonstrates that electrostatic and orbital interactions have equal contributions to stabilize the Ng-Au bonds in the [(FLP)AuNg]+ complex.